Kesetaraan Gender dalam Pengambilan Keputusan Pemanfaatan Pelayanan Kesehatan di Daerah Urban dan Rural, Indonesia - Nyoman Anita Damayanti; Ratna Dwi Wulandari; Ilham Akhsanu Ridlo; Wahdah Dhiyaul Akrimah; Fathiyah Rahmah; Wahyul Anis; Lama’ah Azzahra (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
Utilization of health services by pregnant and postpartum women can save women from the incidence of maternal death and severe complications during pregnancy and postpartum. Several factors that directly contribute to the utilization of health services are decision making and sources of information obtained by pregnant and postpartum women regarding the utilization of health services. This study aims to analyze gender equality in decision making on the use of health services in urban and rural areas of Indonesia. This study used a mixed-method approach from primary data and a literature review. The target in this article was pregnant women and postpartum mothers who were spread out in several health centers in Surabaya City and Bojonegoro Regency with a total of 175 respondents who were calculated using the proportion estimation formula. Data analysis used univariate and bivariate analysis. The results showed that the wife in terms of the number of frequencies dominated in making decisions on the use of health services (92.5%). In addition, when the decision maker is the husband, all postpartum mothers (100%) will take advantage of health services. Related to the source of information that many respondents chose in providing information related to pregnancy health for the use of health services, it was health workers (86.3%) compared to other media. The wife's decision is a determinant in making decisions about the use of health services. On the other hand, husband’s support as a decision maker can also influence his wife to take advantage of health services.